Covalent bonding of zeolitic imidazolate framework-90 to functionalized silica fibers for solid-phase microextraction - Yu, Li-Qing; Yan, Xiu-Ping (Chemical communications (Cambridge, England), 2013)
Here we report a covalent bonding approach to fabricate a robust metal-organic framework ZIF-90 coating for solid-phase microextraction. The ZIF-90 bonded fiber exhibits high enhancement factors, wide linearity, excellent reproducibility, and good lifetime for the studied polar endocrine disruptors.